PENGARUH KONTROL DIRI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN PERILAKU CYBERLOAFING SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada PT Mahaka Radio Integra) - Darrell Monang Pitoy Sompie (2022)
This study uses testing through quantitative methods with the aim of knowing the effect of self-control and organizational commitment on employee performance through cyberloafing behavior as a mediating variable on employees of PT Mahaka Radio Integra. The study used 43 respondents, with saturated sampling technique. The analysis technique used is path analysis and data processing which is carried out through SmartPLS 3.0. the results of the test obtained (1) self-control has a positive and significant effect on employee performance at PT Mahaka Radio Integra, (2) organizational commitment has a positive and significant effect on employee performance at PT Mahaka Radio Integra, (3) self-control has a positive and significant effect on employee performance. PT Mahaka Radio Integra mediated by cyberloafing behavior, (4) organizational commitment has a positive but not significant effect on employee performance of PT Mahaka Radio Integra mediated by cyberloafing behavior, (5) cyberloafing behavior has a positive and significant effect on employee performance at PT Mahaka Radio Integra.